Marphology of building leading to economical project / Mack Mayer Ogit - Ogit, Mack Mayer (2003)
Morphology can be defined as a form of building. The form of building is often determined in the early stage of the project, which is during design stage. Building morphology creates possibilities of cost variation due to the effect of shape and height. In the other part, the level of its major components and the factors that influence their size, quantity and cost. In this study, the era of building form and factors influence the cost of project in Malaysian construction industry are being analyzed. This study is limited to a unique design of tall building and erected at the same characteristic. This is because comparison of such building will help in making decision of choosing the right building morphology and economical to build. Cost is the main target of this study. Postal survey was carried out on the Malaysian Construction Companies as listed in the CIDB Directory. Case studies were carried out in order to give a better view of the implementation of building morphology and its benefits and the achievements in such building form. Studies were made of two same characteristics of project, which are PNB and LUTH building.